Réanalyse des formes des marqueurs de classe du pulaar (peul) sous l’éclairage de la réduplication - Niang Oumar (Corela)
This article proposes to examine the class marker of Pulaar, Fulani language, from the perspective of reduplication. The latter intervenes within the framework of the nominal determination and substitution. The analysis of the reduplicated marker leads to a new distribution of variant forms of class morphemes in this language.